An Analysis Of Discovery Learning Model Used in Teaching Narrative Text at Tenth Grade of SMAN 1 Koto Salak Dharmasraya - Susanti, Yesi; Asty, Herfyna; Sesmiyanti, Sesmiyanti (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2022)
This research was motivated by application of the Discovery Learning Model by an English Teacher who teach at tenth grade of SMAN 1 Koto Salak. The researcher wants to know how the teacher applies the discovery Learning Model used in teaching narrative text. Then, this research uses a qualitative method with an autobiography case study that aims to analyze and see from the personal experience of a teacher in delivering learning materials in narrative text. Meanwhile, participant in this study was a teacher who teaches English at tenth grade and has applied the Discovery Learning Model. Data collection was carried out by researcher uses interviews. Based on the data analysis, it can be concluded that the English teacher has implemented the principles of discovery learning Model well, namely the teacher forms students into several groups, the teacher provides opportunities to complete assignments or problems that have been given according to the subject matter, the teacher facilitate students to collect information through books and internet, teachers assist students in gathering information, and ask students to present their findings in front of class. In conclusion, it can be said that Discovery Learning Model applied by English teacher at SMAN 1 Koto Salak is going well.